(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. Modern medical contracts are undergoing significant transformations due to the widespread adoption of digital technologies and telemedicine. This article examines key aspects of the evolving contractual relationships in healthcare, including the regulation of remote consultations, electronic documentation, personal data protection, and liability of the parties. Special attention is given to legal innovations, international best practices, and practical recommendations for healthcare organizations. The article aims to analyze current trends and identify optimal approaches to drafting medical contracts in the context of industry digitalization.